Sex difference in the effect of time from symptoms to surgery on benefit from carotid endarterectomy for transient ischemic attack and nondisabling stroke. - Rothwell, P; Eliasziw, M; Gutnikov, SA; Warlow, C; Barnett, H (2004)
BACKGROUND AND PURPOSE: Early studies showed that carotid endarterectomy (CEA) carried a high risk if performed within days after a large ischemic stroke. Therefore, many surgeons delay CEA for 4 to 6 weeks after any stroke. To determine the effect of delay to CEA on operative risk and benefit, we pooled data from the North American Symptomatic Carotid Endarterectomy Trial and the European Carotid Surgery Trial. METHODS: Risk of ipsilateral ischemic stroke in the medical group, operative risk of stroke and death, and overall benefit from surgery were determined in relation to the time from the last symptomatic event to randomization. Operative risk of stroke and death was also determined in relation to the time to surgery. Analyses were stratified by sex and type of presenting event. RESULTS: The 30-day perioperative risk of stroke and death was unrelated to the time since the last symptomatic event and was not increased in patients operated <2 weeks after nondisabling stroke. In contrast, the risk of ipsilateral ischemic stroke in the medical group fell rapidly with time since event (P<0.001), as did the absolute benefit from surgery (P=0.001). This decline in benefit with time was unrelated to the type of presenting event but was more pronounced in women than men (difference P<0.001). Benefit in women was confined to those randomized <2 weeks after their last event, irrespective of severity of stenosis. CONCLUSIONS: CEA can be performed safely within 2 weeks of nondisabling ischemic stroke. Benefit from endarterectomy declines rapidly with increasing delay, particularly in women.